D'Après : Da Anzinger a Warhol. - Anton, Eleanore; Anzinger, Siegfried; Avveduti, Sergia; Ayrton, Michael; Evergon; Fogli, Andrea; Gil, Javier; Hilliard, John; Kolar, Jiri; Kunc, Milan; Lawler, Louise; Mariani, Carlo Maria; et al. (Torino : Gas Art Gallery Torino, 2003)
Antin, Eleanor ; Anzinger, Siegfried ; Avveduti, Sergia ; Dugdale, John ; Evergon ; Fogli, Andrea ; Gil, Javier ; Hilliard, John ; Knap, Jan ; Kolar, Jiri ; Kunc, Milan ; Lawler, Louise ; Mariani, Carlo Maria ; Massini, Claudio ; Morimura, Yasumasa ; Muniz, Vik ; Nespolo, Ugo ; Ontani, Luigi ; O'Reilly, John ; Padgett, Laura ; Pisani, Vettor ; Poirier, Anne & Patrick ; Rainer, Arnulf ; Salvo ; Scheda, Stefano ; Silombria, Marco ; Spero, Nancy ; Tobreluts, Olga ; Trenkwalder, Elmar ; Warhol, Andy ; Ziegler, Michael
biog. p.66-73
Italiaans
Exhibition. D'Après : Da Anzinger a Warhol. Gas Art Gallery Torino, 13.03.2003 - 03.05.2003.
boek